Poly(arylene piperidinium) terpolymer membranes with dual piperidinium cations and semi-fluoroalkyl pendants for anion exchange membrane water electrolyzers - Yadav, Vikrant; Miyatake, Kenji; Ahmed Mahmoud, Ahmed Mohamed; Liu, Fanghua; Xian, Fang; Guo, Lin; Wong, Chun Yik; Iwataki, Toshio; Uchida, Makoto; Kakinuma, Katsuyoshi (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
To develop high-performance anion exchange membranes (AEMs), the effect of the length of semi-fluoroalkyl pendants on physical and electrochemical properties of the resulting AEMs was investigated. A series of 2,5-dichlorobenzene monomers differing in semi-fluoroalkyl pendant length were synthesized and copolymerized with 2,2-bis(4-chlorophenyl)hexafluoropropane and piperidine functionalized 2,7-dichlorofluorene. The terpolymers provided bendable membranes by solution casting. The membranes with comparable ion exchange capacity (IEC = ca. 1.85 meq g −1 ) showed similar water uptake, while the hydroxide ion conductivity increased by 24% on increasing the pendant chain from 7 to 11 carbons. The maximum ion conductivity of 112 mS cm −1 (at 80 °C) was achieved for the membrane formulated with the C 11 pendant. C x -QPip- n membranes showed good alkaline stability; in particular, C 11 -QPip-1.86 retained 75% of the original conductivity after 1056 h under harsh alkaline conditions (8 M KOH at 80 °C). An alkaline water electrolysis cell assembled with the C 11 -QPip-1.86 membrane and with a PGM-free anode catalyst (Ni 0.8 Co 0.2 O) showed good performance (1.0 A cm −2 at 1.64 V) with high voltage efficiency (75%). The cell was durable for 1000 h with minor voltage change (28 μV h −1 ) under constant current density (1.0 A cm −2 ) operation. The effect of the length of semi-fluoroalkyl pendants on physical and electrochemical properties was investigated for poly(arylene piperidinium) terpolymer-based anion exchange membranes for applications in alkaline water electrolyzers.